Edukasi Penggunaan Aplikasi Akuntansi UKM - Trisulo, Trisulo; Lawi, Kresensia Berliana; Sianturi, Indra Polma; Napitupulu, Danny Haryanto (Journal Pemberdayaan Masyarakat Indonesia, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are trading businesses or economic activities carried out by individuals or groups of people who have a role in Indonesia's economic development. The existence of MSMEs which have a major role in the economy needs to be maintained and developed so that they can provide more benefits for the community and the Indonesian economy. The problem for MSMEs today is the lack of ability and knowledge in the field of accounting, especially in recording and making financial reports. The PKN STAN Community Service Program is integrated with the Student Work Lecture (KKM) conducted by the Ak 106 group to help MSME actors to have the ability to manage their finances. The activity focused on providing technical guidance related to the use of SME Accounting applications to partners who own Halal Mart SMEs in Duri City, Bengkalis Regency, Riau. The method used in educating the use of SME Applications is the training and visiting system (LAKU) method, intending to help partners record and prepare financial reports. As a result of these activities, MSME Halal Mart partners can use the Android-based SME Accounting application and realize the benefits and ease of recording accounting using the application.